Systemic Crisis in the US-Turkish Relations Under the Presidency of D. Trump - A. A. Davydov (Vestnik MGIMO-Universiteta)
Relations between the United States and Turkey, the two military-political allies of the North Atlantic Treaty Organization (NATO), are experiencing an unprecedented crisis in their history. Its depth and scale is so significant that it affects the long-term foreign policy strategies of both countries, as well as the process of building a unified security architecture. In the study the author raises a question to what extent the current crisis in the US-Turkish relations is systemic? How high is the probability that it will turn out to be a long-term one? To answer this question, the study is divided into two parts.The first part analyzes the evolution of American approaches to Turkey in US foreign policy, the implementation of these approaches since the end of World War II till nowadays. On the basis of a system-historical approach, the author analyses the evolution the Turkey’s strategic positioning in the US foreign policy strategy and the transformation of political, economic and military relations between the two states since the moment of their institutionalization. The author distinguishes two stages of this evolution. During the first one, for the United States Turkey was one of the key countries that was blocking the Soviet expansion southward towards the Persian Gulf and the Suez Canal. The author notes that by the end of the bipolar confrontation, Turkey was de-facto losing its functional purpose in the logic of the Cold War. During the second stage, the US regards Turkey as one of the key NATO allies, whose geo-strategic location can be used for pursuing American national interests in the nearby regions. Author posits, that bilateral relations are gradually moving away from such a model of interaction. This happens because of the Turkish desire to diversify foreign relations and accumulation of contradictions between Washington and Ankara due to the divergence of their foreign policy strategies.The second part analyzes the contradictions in the American-Turkish relations under the presidency of Donald Trump on political, military and economic issues. The author comes to the conclusion that the crisis is indeed a systemic one. Firstly, the existing problems began to affect significant elements of the military-technical infrastructure of their relations. Secondly, it is difficult to resolve these problems without reformatting the interaction as between equivalent actors of international relations. Thirdly, the expert and political communities have not presented any kind of a new approach to rethink the allied status of American-Turkish relations.